Proceedings of the 39th SIGCSE Technical Symposium on Computer Science Education 2008
DOI: 10.1145/1352135.1352252
|View full text |Cite
|
Sign up to set email alerts
|

Evolving an integrated curriculum for object-oriented analysis and design

Abstract: Object-Oriented Analysis and Design has established itself as an integral and critically vital part of the software development process. In this paper, we describe an integrated approach to teaching this subject so that it covers vital components of this vast field: analysis, object-oriented design principles such as the Liskov Substitution Principle, the design process, which shows how and where the rules are applied, modeling, design and architectural patterns, language features, and refactoring. The course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Lin et al [11] developed a heuristic teaching method for object-oriented analysis and design courses to address the learning of new ideas, ways of thinking, and symbolization issues of students and to improve the effectiveness of teaching. Ramnath [12] proposed a comprehensive method for teaching object-oriented analysis and design that emphasizes the interrelationships between all important aspects and their relevance to the design process. Feedback showed that this method improved the students' understanding of OOAD concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lin et al [11] developed a heuristic teaching method for object-oriented analysis and design courses to address the learning of new ideas, ways of thinking, and symbolization issues of students and to improve the effectiveness of teaching. Ramnath [12] proposed a comprehensive method for teaching object-oriented analysis and design that emphasizes the interrelationships between all important aspects and their relevance to the design process. Feedback showed that this method improved the students' understanding of OOAD concepts.…”
Section: Literature Reviewmentioning
confidence: 99%